1988
DOI: 10.1093/jn/118.8.1024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bovine Somatotropin on Metabolism of Lactating Dairy Cows: Energy and Nitrogen Utilization as Determined by Respiration Calorimetry

Abstract: Effects of exogenous bovine somatotropin (bST) on energy and nitrogen utilization by high producing dairy cows were examined. Nine cows received bST (51.5 IU/d) or exipient (control) in a single reversal design involving 14-d treatment periods. Energy and nitrogen balances were measured in open-circuit respiration chambers. Yield of 4% solids-corrected milk was increased by 22% with bST treatment. Dry matter intake and the apparent digestibilities of dry matter, energy and nitrogen were not altered by treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
2
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 16 publications
0
27
2
3
Order By: Relevance
“…for 14 days increase milk production without affecting fat and protein (Ludri et al, 1989) contrary to increased fat, protein and lactose observed in this study. The reasons of such short term treatment on milk composition of buffaloes require further investigation as milk composition is influenced by energy balance and mobilization of body reserves (Eppard et al, 1985;Peel et al, 1982 andTyrrell et. al.…”
Section: Discussionmentioning
confidence: 99%
“…for 14 days increase milk production without affecting fat and protein (Ludri et al, 1989) contrary to increased fat, protein and lactose observed in this study. The reasons of such short term treatment on milk composition of buffaloes require further investigation as milk composition is influenced by energy balance and mobilization of body reserves (Eppard et al, 1985;Peel et al, 1982 andTyrrell et. al.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, rates of protein synthesis for the whole mammary gland exceed protein output by 25-38% (Bequette et al 1996b), but how this additional synthesis is partitioned between turnover of milk and constitutive proteins in the udder is unknown. Furthermore, although the mammary gland may contribute 40-42% of whole body protein flux (Bequette et al 1996b), the gland only consumes 7-14% of whole body oxygen (from Tyrrell et al 1988;Guinard and Rulquin 1995;Thivierge et al 2002) so, again, the link between protein turnover and energy expenditure is not strong at the tissue level. This is not too surprising as it would be "unwise", in evolutionary terms, for homeothermic reliance on an organ the metabolic activity of which varies considerably with both stage of lactation and nutrient supply.…”
Section: Tissue Protein Synthesismentioning
confidence: 99%
“…Feed, faecal and urinary N and C were determined respectively using the Kjeldahl procedure and by combustion in an atmosphere of oxygen with volumetric determination of CO 2 produced (Smith et al 1965). All moisture determinations were made by drying to a constant weight in a forced draft oven at 100 C. Milk samples collected daily over two consecutive milkings were analysed for true milk protein and fat percentages by infrared analysis (Moe et al 1972(Moe et al , 1973Tyrrell and Moe 1974;Tyrrell et al 1988;Sechen et al 1989;Andrew et al 1991). A list of measured variables and their summary statistics are given in Table 1.…”
Section: Data Sourcesmentioning
confidence: 99%